Caryatids lost and regained: rebranding the classical body in contemporary Greece. (Journal of Greek Media & Culture, 2017)
This article examines patterns of reception through which a particular type of classical sculpture – the Caryatid – has been accepted into the cultural life of contemporary Greece. Loved by neoclassical architecture, though also prominent in Modern Greek design, as well as contemporary poetry and drama, the Caryatid serves as a logo for the country and the Greeks at large, especially when referring to their relations with their fellow-Europeans. In contemporary Greek culture, Caryatids are deployed as symbols of Greekness as well as a means to achieve the nation’s cultural emancipation against the supremacy of western, globalised modernity. Often derided as mere symptoms of colonial mimicry, through their inherent qualities of parody and subversiveness, such uses may sometimes prove unexpectedly successful in undermining modernity and its templates.